Neural Oscillations and the Initiation of Voluntary Movement - Armstrong, Samuel; Sale, Martin V.; Cunnington, Ross (Frontiers in Psychology, 2018)
The brain processes involved in the planning and initiation of voluntary action are of great interest for understanding the relationship between conscious awareness of intentions and the neural control of movement. Voluntary motor behaviour has generally been considered to occur when conscious intentions trigger movements. However, several studies now provide compelling evidence that brain states indicative of forthcoming movements take place before a person becomes aware of a conscious intention to act. While such studies have created much debate over the nature of free will, at the very least they suggest that unconscious brain processes are predictive of forthcoming movements prior to a person’s conscious intention to act. Recent studies suggest that slow changes in neuroelectric potentials may play a role in the timing of movement onset by pushing brain activity above a threshold to trigger the initiation of action. Indeed, recent studies have shown relationships between the phase of low frequency oscillatory activity of the brain and the onset of voluntary action. Such studies, however, cannot determine whether this underlying neural activity plays a causal role in the initiation of movement or is only associated with the intentional behaviour. Non-invasive transcranial alternating current brain stimulation can entrain neural activity at particular frequencies in order to assess whether underlying brain processes are causally related to associated behaviours. In this review we examine the evidence for neural coding of action as well as the brain states prior to action initiation and execution and discuss whether low-frequency alternating current brain stimulation could be used to influence the timing of person’s conscious decision to perform a voluntary action.